Analysis of the Gap Clearance of Harmonic Gear Reducer - Long Wang; Bo Liu; Jiabo Zhang; Hongxing Li; Qing Wang (Jixie chuandong)
The sources of the harmonic gear reducer gap clearance are complicated， the gap clearance is the main factor affecting the operation accuracy of the mechanism. According to the work principle of the harmonic gear reducer， the main factors causing the gap are the torsional deformation of the parts（the flexible wheel and output shaft），and the clearance between the rigid and flexible wheels， and the radial clearance of the flexible bearing. Secondly， using the theory of involute， material mechanics， stiffness and so on， the mathematical model of the gap clearance and above factors is established. Finally， a gap-free test of one kind of harmonic gear reducer is carried out， the measured results are in good agreement with the theoretical calculation.